2014
DOI: 10.1371/journal.pone.0096710
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decrease of Meiotic Cohesins in Human Oocytes

Abstract: Aneuploidy in fetal chromosomes is one of the causes of pregnancy loss and of congenital birth defects. It is known that the frequency of oocyte aneuploidy increases with the human maternal age. Recent data have highlighted the contribution of cohesin complexes in the correct segregation of meiotic chromosomes. In mammalian oocytes, cohesion is established during the fetal stages and meiosis-specific cohesin subunits are not replenished after birth, raising the possibility that the long meiotic arrest of oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 32 publications
7
100
1
1
Order By: Relevance
“…During the long prophase arrest that precedes meiosis I in female mammals, cohesin levels decline gradually and in aged oocytes this reduction in cohesin causes destabilization of chiasmata and separation of sister centromeres, which can result in chromosome missegregation during meiosis I (Lister et al, 2010;TachibanaKonwalski et al, 2010;Tsutsumi et al, 2014). This current study determined that SMC5/6 protein levels decrease in oocytes isolated showing even metaphase I to anaphase I chromosome segregation (MI to AI even), chromosome stretching (MI to AI stretch); and in anaphase I (n=40 for control and n=53 for Smc5 cKO) showing no lagging chromosomes (AI no lagging) and lagging chromosomes (AI lagging).…”
Section: Smc5/6 Protein Levels Are Diminished In Aging Oocytesmentioning
confidence: 99%
“…During the long prophase arrest that precedes meiosis I in female mammals, cohesin levels decline gradually and in aged oocytes this reduction in cohesin causes destabilization of chiasmata and separation of sister centromeres, which can result in chromosome missegregation during meiosis I (Lister et al, 2010;TachibanaKonwalski et al, 2010;Tsutsumi et al, 2014). This current study determined that SMC5/6 protein levels decrease in oocytes isolated showing even metaphase I to anaphase I chromosome segregation (MI to AI even), chromosome stretching (MI to AI stretch); and in anaphase I (n=40 for control and n=53 for Smc5 cKO) showing no lagging chromosomes (AI no lagging) and lagging chromosomes (AI lagging).…”
Section: Smc5/6 Protein Levels Are Diminished In Aging Oocytesmentioning
confidence: 99%
“…Oxidative stress is likely to impact several pathways within the cell and damage of meiotic spindle components, kinetochores, or the spindle assembly checkpoint (SAC) could lead to meiotic segregation errors in older oocytes (62-65). However, because there is evidence that cohesion deteriorates with age (8,(11)(12)(13)(14)(15)(16)(17)(18), and because NDJ is more pronounced when SOD is knocked down in mtrm +/− oocytes, we were specifically interested in examining the effect of oxidative stress on the integrity of meiotic cohesion.If SOD KD leads to premature loss of cohesion, then oocytes with a reduced level of functional cohesin may be more susceptible to the effect of SOD KD on NDJ. To test this possibility, we used females heterozygous for a deletion of the smc1 gene (smc1Δ/+) in which the protein level of the cohesin subunit SMC1 is lowered (11), but still adequate to support accurate meiotic chromosome segregation (11) (Fig.…”
mentioning
confidence: 99%
“…The rate of a trisomy increases greatly from nearly 2% for women in their 20s to 35% for women in their 40s (13). A recent study has suggested that the deterioration of cohesins might be responsible for age-related aneuploidy (22). In mice, this phenomenon is thought to be related to the strain.…”
Section: Discussionmentioning
confidence: 99%
“…Since the density of the cohesin subunit STAG3 changes little in the ovarian aging process (22), the current study only detected the levels of three cohesin subunits: REC8, SMC1β, and SMC3. Ovarian slides were blocked and then incubated with primary and secondary antibodies as described (37).…”
Section: Immunofluorescent Stainingmentioning
confidence: 99%
See 1 more Smart Citation